Comparative Analysis Of The Image Of Nightingale And Crow - Mokhichekhra Mukhammadiyeva (Zien Journals, 2024)
This article compares and analyzes the image of a crow and a nightingale. Their symbolic and figurative meanings in works of art are explained. Information about the origin of the image of the crow and its biological characteristics is provided
Keywords: Symbol; crow; nightingale